Answer:
![\large\boxed{g(-1)=4}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z3szyz38tcy5wbavgkhfakf14csadh5h05.png)
Explanation:
In this question. we would be plugging in -1 to all of the x variables.
The equation we are solving is:
![g(x)=(3x^2-2x+7)/(2x+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cw865due8tm80za01ezf84phqw0ikn7mtl.png)
You would plug in -1 to all of the x variables.
Your equation should look like this:
![g(x)=(3(-1)^2-2(-1)+7)/(2(-1)+5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/16lk4lwfjoh1fmavxlaw8cm8cy9v5ajrbf.png)
Now, you solve:
![g(x)=(3(-1)^2-2(-1)+7)/(2(-1)+5)\\\\\text{Lets start with the top}\\\\g(x)=(3(1)-2(-1)+7)/(2(-1)+5)\\\\g(x)=(3-2(-1)+7)/(2(-1)+5)\\\\g(x)=(3+2+7)/(2(-1)+5)\\\\g(x)=(12)/(2(-1)+5)\\\\\text{We can do the bottom now}\\\\g(x)=(12)/(2(-1)+5)\\\\g(x)=(12)/(-2+5)\\\\g(x)=(12)/(3)\\\\\text{Divide the fraction}\\\\g(-1)=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t8xrk620dk5uqxt9wmowpghw67rbidzdjm.png)
When you're done solving, you should get 4.
This means that when g is -1, the answer would be 4.
g(-1) = 4
I hope this helped you out.
Good luck on your academics.
Have a fantastic day!